Risk Mitigation on Supply Chain of Rice: Case Study at Demak and Sleman Districts - Adi Djoko Guritno; Novita Erma Kristanti; Megita Ryanjani Tanuputri (agriTECH, 2018)
Rice is a vital commodity in Indonesia because it is the main staple food for most Indonesian people.  Balancing supply and demand of rice in Indonesia is complex and has possibly led to polemics, even though the production of rice in Indonesia tends to increase. An analysis of the supply-demand for rice commodity is, therefore, necessary as an effort to improve the national rice condition along with the logistics and supply chain point of view. This study aims to analyze the supply chain risk management of rice to provide recommendations on improving rice supply chain performance on each tier. This study was undertaken at Demak and Sleman Districts, Indonesia. In-depth interviews were used to enrich the information from the respondents along the supply chain. In this study, tiers on the supply chain of rice mainly consists of farmers, collectors who also acts as traders, and retailers. Meanwhile, the role of government is represented by The Indonesia Logistics Bureau (BULOG). The different supply chain pattern could be identified from the role of middleman in each province. This study uses ISO 31000:2009 standard for analyzing the risk in each tier along the supply chain. Based on the risk analysis, on-farm activity plays a vital role in transferring risk along the supply chain in terms of quality and quantity. Risk mitigation of each tier was explored in this study.